FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH KOTA MALANG (STUDI PADA SKPD DI PEMERINTAH KOTA MALANG) - Stefani Claudia Paramita (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research was aimed to determine the effect of internal control system, human resource competency, and utilization of information technology on the quality of financial statement at the Government of Malang City. This research used a quantitative approach, with using primary data through questionnaires. Respondents of this research were Financial Manager, Head of Financial Division, and Staff of Financial Division from 34 SKPD at Government of Malang City. Out of 102 questionnaires distribution, 73 usable questionnaires were gathered. The statistical methods used to test is multiple linear regression analysis.   The result of research shown that the internal control  system,  human resource competency,  and  the utilization  of information technology give the impact add it was positive to the quality of financial statements at the Government of Malang City.Keywords : Internal control system, human resource competency, utilization of information     technology, quality of regional government financial statement